2020
DOI: 10.1002/cncy.22349
|View full text |Cite
|
Sign up to set email alerts
|

Significant reduction of indeterminate (atypical) diagnosis after implementation of The Paris System for Reporting Urinary Cytology: A single‐institution study of more than 27,000 cases

Abstract: Background Urinary cytology is a noninvasive and cost‐effective diagnostic and surveillance test in the clinical management of urothelial carcinoma (UC). The Paris System for Reporting Urinary Cytology (TPS), published in 2016, introduced definite diagnostic criteria aimed at improving performance in detecting high‐grade UC (HGUC) and decreasing the indeterminate (atypical) diagnosis. Methods The authors retrospectively reviewed and compared urinary cytology diagnoses reported between January 2013 and December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…The overall figures decreased from 18.6% to 14.4% and in voided urine the decrease in AUC diagnoses was from 20% to 14.5%. 19 Still, other studies have shown a decrease in AUC diagnoses in both instrumented (36.6% to 9.1%) and voided (26.9% to 6.0%) urine samples, 20 although instrumented samples had a higher AUC rate. According to some authors, instrumentation artifacts may enhance nuclear border irregularities and 10 Cowan et al 4 reported the post-TPS ROM in the AUC category as 7%-53% in comparison to the pre-TPS range of 28.3%-33%.…”
Section: Discussionmentioning
confidence: 88%
“…The overall figures decreased from 18.6% to 14.4% and in voided urine the decrease in AUC diagnoses was from 20% to 14.5%. 19 Still, other studies have shown a decrease in AUC diagnoses in both instrumented (36.6% to 9.1%) and voided (26.9% to 6.0%) urine samples, 20 although instrumented samples had a higher AUC rate. According to some authors, instrumentation artifacts may enhance nuclear border irregularities and 10 Cowan et al 4 reported the post-TPS ROM in the AUC category as 7%-53% in comparison to the pre-TPS range of 28.3%-33%.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, Tian et al (2020) chronologically reviewed and retrospectively compared urine cytology diagnoses between pre-TPS and post-TPS, and described that all categories in urine cytology had superior correlation with UroVysion results by post-TPS, and positive UroVysion results increased from 87% to 93% in suspicious for HGUC category. By these results, it is hopeful that application of TPS could lead to significant reduction of atypical UC diagnosis, and potential cost effectiveness (60).…”
Section: The Role Of Urovysion In the Era Of Diagnosis Based On The Paris System On Reporting Urinary Cytology (Tps) Since 2016mentioning
confidence: 90%
“…From its implementation, it has been shown to enhance correlation with histology, especially when the low urinary tract is sampled, while decreasing the indeterminate diagnoses [46,47]. Indeed, a few studies have demonstrated that TPS has reduced the rate of atypical interpretations reported in their departments [48][49][50][51]. This finding has a great clinical significance, as before the implementation of TPS, many urologists were regarding atypical cases as negative [6].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, TPS focuses on what is more important, which is the detection of HGUC [1,7]. Thus, it has established strict criteria for each one of its categories, including AUC, aiming to identify HGUC rather than LGUN, resulting in a frequency reduction in the "atypical" interpretations compared to the pre-TPS era [48][49][50][51]. Of interest, the pooled ROHM of the AUC reporting category in our meta-analysis was found to be 38.65% (95% CI, 0.3042; 0.4759), which should warrant close clinical follow-up and/or the use of ancillary testing [1,7], rather than being regarded as negative.…”
Section: Discussionmentioning
confidence: 99%